Reforming Corporate Financial Reporting : Lessons from REPARIS for Other Technical Assistance Programs - Owen, James; Sekiguchi, Juri (World Bank, Washington, DC, 2014)
The recent financial crisis brought to light the importance of transparent and effective corporate financial reporting to a country s economic recovery and subsequent growth. The Road to Europe: Program of Accounting Reform and Institutional Strengthening (REPARIS) program, supported with technical assistance from the World Bank, was designed to assist its eight participating member countries in improving their institutional frameworks for corporate financial reporting and fostering the adoption of European Union (EU) standards for business reporting and auditing. This program has been used to build the kind of broad stakeholder support, both public and private, that is vital for the successful implementation of financial reporting reforms. The emphasis on peer learning, through such tools as communities of practice, helps promote the effective implementation of reforms. In-country engagement is also critical to ensure that changes are implemented on the ground.